Thermal and mechanical properties of thermoplastic cassava starch/beeswax reinforced with cogon grass fiber - Jumaidin, Ridhwan; Abdul Halim, Harith Hilman; Mohammad Taha, Mastura; Ab Ghani, Ahmad Fuad; Mustafa, Nuzaimah; Zakaria, Nazri Huzaimi; Abdul Kudus, Syahibudil Ikhwan; Yaakob, Mohd Yuhazri; Aziz, Alia Ruzanna; Keshavarz, Meysam; Salleh, Tuan Suhaimi; Rushdan, Ahmad Ilyas; et al. (Semarak Ilmu, 2022)
The aim of this paper is to investigate the effect of cogon grass fiber (CGF) on the thermal and mechanical properties of thermoplastic cassava starch (TPCS)/beeswax matrix. The alteration of TPCS/beeswax reinforced with cogon grass fiber was performed by incorporating various amount of CGF (0,10,20,30,40 wt.%) into the polymer matrix. The samples were then evaluated using thermogravimetric analysis and tensile test. The findings showed that the thermal properties of the composite were slightly improved as the CGF content increase. The mechanical test showed that the tensile strength and tensile modulus increased with the addition of the CGF. However, the elongation at break showed a decreased pattern following the increasing content of CGF compared to the 0% of fiber content. In general, the findings from this study have shown that the TPCS/beeswax reinforced with the CGF composite has improved the functional properties of the composites compared to the TPCS matrix.